The Effect of Legal Education on Public Legal Awareness - Febrianty, Yenny; Ariyanto, Ariyanto; Fitri, Hidayati; Ryendra, Nadya Restu (Journal of Public Representative and Society Provision, 2025)
This study examines the impact of legal education on public legal awareness in Indonesia, using a quantitative cross-sectional survey design. The research investigates how participation in legal education programs influences individuals' understanding of legal rights, processes, and access to justice. A total of 500 respondents, stratified by demographic factors such as gender, age, education level, and geographic location, were surveyed. The findings reveal that individuals who participated in legal education programs reported significantly higher legal awareness (M = 4.10) compared to those who did not (M = 3.30), with a large effect size (Cohen's d = 0.80). Demographic factors such as education level, employment status, and age were also found to influence legal awareness, with higher educational attainment and employment status positively correlating with increased legal awareness. Gender-based differences were observed, but their practical significance was minimal. Regression analysis further confirmed that legal education is a significant predictor of legal awareness (β = 0.62, p < 0.001). The results emphasize the crucial role of legal education in fostering an informed and engaged citizenry, particularly in enhancing public understanding of legal rights and responsibilities. The study suggests that increasing access to legal education can lead to a more empowered society, capable of participating actively in legal and civic processes.